Carbene-based bioadhesive blended with amine, thiol, and acrylate liquid additives - Ellis, Elizabeth (2023)
Light activated carbenes provide a unique method of non-specific covalent bond formation needed in bioadhesives and rapid gelation. The highly reactive carbenes formed upon UV irradiation allow for binding to a wide range of natural and synthetic substrates in addition to cohesive bonds. However, little is known about how these crosslinkers would behave in the presence of additives, which are important for tuning material properties. This work investigates carbene based bioadhesives in the presence of various liquid additives containing reactive functional groups of hydroxyl, thiol, amine, or acrylate. Steady shear viscosity, dynamic mechanical properties, microstructure, and reactive functional groups are evaluated by photorheometry, scanning electron microscopy (SEM), and FTIR spectroscopy. The triol hydroxy additive maintains the storage modulus despite dilution of the diazirine crosslinker. The thiol additive reduces apparent viscosity whilst maintaining material properties. Polyamine accelerates ester hydrolysis and increases hydrophilicity. For the first time diacrylate polymerization is demonstrated by photoactivated diazirine, the carbene precursor. The diacrylate additive displays synergistic enhancement of dynamic modulus within the binary composite, reaching 977 kPa compared to 82 kPa of neat carbene based bioadhesive. The polymerisation of acrylates initiated by diazirine photolysis opens possibilities for acrylate initiation and hybrid composite biomaterials.